“I turned back my feet to your decrees” (Psalm 119:59) : Torah in the Fifth Book of the Psalter, Michael Kodzo Mensah - Botha, Phil J. (Journal for Semitics, 2016)
This book is the result of intensive research into the structure of Ps 119, the development of its thought, and the way in which the concept of Torah (which is central to this long psalm) also plays a role in Book V of the Psalter. It was originally presented as a thesis by the author, Michael Mensah, a scholar from Ghana, at the Pontifical Biblical Institute in Rome and the imprint of the eminent Prof. Gianni Barbiero, who acted as supervisor, is evident in more ways than one.
free